1966
DOI: 10.1099/00221287-45-2-213
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Changes in the Concentrations of Micro-organisms in the Rumens of Sheep Fed Limited Diets Once Daily: WITH AN APPENDIX ON THE KINETICS OF RUMEN MICROBES AND FLOW

Abstract: SUMMARYThe pattern of change of concentration of different groups of microorganisms in the rumen was found to be characteristic of the group and little affected by the time of day, the nature of the diet, or the host animal. The dilution rate of rumen liquor and the rate of change of concentration of several groups of micro-organisms were measured a t intervals following feeding; this allowed calculation of the apparent specific growth rate. The changes in concentration of the ophryoscolecid ciliate protozoa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
1

Year Published

1975
1975
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 11 publications
6
54
1
Order By: Relevance
“…A significant treatment by time interaction was detected in that the concentration of protozoa was significantly lower for SH treatment only at T0. All three treatments showed similar quadratic curves, i.e., a decrease in concentration at 3 h post feeding followed by a slight increase at 6 h. This behaviour agrees with the diurnal changes reported 26,27,28 and might indicate the dilution effect from eating. However, methanogenic bacteria were not determined in this study because of the symbiotic relationship between protozoa and methanogenic bacteria; it was described 15 that the decrease in the number of protozoa when the animals were fed the SH diet could suggest a decrease in the number of methanogenic bacteria which in turn would lead to an increased production of propionic acid 15 .…”
Section: Effects On Rumen Bacteriasupporting
confidence: 86%
“…A significant treatment by time interaction was detected in that the concentration of protozoa was significantly lower for SH treatment only at T0. All three treatments showed similar quadratic curves, i.e., a decrease in concentration at 3 h post feeding followed by a slight increase at 6 h. This behaviour agrees with the diurnal changes reported 26,27,28 and might indicate the dilution effect from eating. However, methanogenic bacteria were not determined in this study because of the symbiotic relationship between protozoa and methanogenic bacteria; it was described 15 that the decrease in the number of protozoa when the animals were fed the SH diet could suggest a decrease in the number of methanogenic bacteria which in turn would lead to an increased production of propionic acid 15 .…”
Section: Effects On Rumen Bacteriasupporting
confidence: 86%
“…The entire cycle occurs within the rumen and the organism could be cultured in vitro; the conditions under which maximum reproduction occurred (39 "C, pH 6.5, absence of oxygen, presence of CO,) indicated that neocallimastix is a true rumen organism since conditions within the rumen are essentially similar (Hungate, 1966). This is supported by the wide distribution of neocallimastix in ruminants (Braune, 1913;Das Gupta, 1935;Eadie, 1962;Warner, 1966). The possession of a rhizoid by the reproductive body shows that the organism may be fungal rather than protozoal ; protozoal reproductive bodies do not normally possess rhizoids.…”
Section: Discussionmentioning
confidence: 60%
“…Fluctuations as high as this are abnormal for rumen organisms, which normally divide only 2 to 4 times a day (Hungate, 1966). Warner (1966) suggested that the cause of this dramatic fluctuation was that the neocallimastix were normally sequestered on the rumen wall, entered the rumen fluid in response to a chemical stimulus in the diet and later returned to the wall by another chemotactic response, possibly to a compound diffusing from the blood into the rumen. This theory was discounted by Orpin (1974) who showed that the neocallimastix population density could be increased in vivo and in vitro by an extract of oats.…”
Section: G O R P I Nmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, zoospores of anaerobic fungi were known since the early part of this century but were mistakenly identified as protozoan flagellates in rumen fluid (Liebetanz, 1910). According to Warner (1966), these flagellates were sequestered on the rumen epithelium, moving to the rumen fluid when the animal was feeding. This hypothesis was necessary to account for the large increase in protozoan flagellates in rumen fluid immediately after feeding.…”
mentioning
confidence: 99%